Research on the influence of indoor relative humidity on PM2.5 concentration in residential buildings - Zhang, Ji (2020)
This study presented an experimental analysis to investigate the influence of the RH on PM2.5 concentration in a typical residential building in Tianjin, China. PM2.5 concentrations were measured using an aerosol monitor in different conditions of three RH scenarios, two pollutant sources and two initial pollutant concentrations. It was observed that about 95% of the size of particles produced by cigarette and wormwood are smaller than 1μm, and the particulate matters produced by wormwood has smaller particle size than that produced by cigarette. Results shows humidification is a practicable method to accelerate the deposition rate of PM2.5. Furthermore, the larger the particle size, and the higher initial pollutant concentration, the more significant influences of the RH on PM2.5 concentration. Considering the requirement of human comfort, the RH is recommended to be controlled at the range of 60%-70% when the indoor PM2.5 pollution is serious. Although humidification can reduce indoor PM2.5 concentration to a certain extent, it cannot reduce the PM2.5 concentration to the permissible range in a short period of time. Therefore, it is recommended to use RH control together with purification device.